Síntese Eco-Friendly: Transformando Clinoptilolita em zeólita do tipo LTA - Lima, Renata Cibely Freire de (2021)
Clinoptilolite is an aluminosilicate, with a zeolitic structure, found in large quantities in nature, however almost unexplored. To expand the applications of this material, an alternative would be to use this natural zeolite for the synthesis of a zeolite of greater industrial interest, such as LTA zeolite structure. Thus, the objective of this work was to use Clinoptilolite as an alternative source in the synthesis of LTA zeolite, varying the synthesis conditions. Clinoptilolite was used as an alternative source of Si and Al in the synthesis of LTA zeolite, varying the crystallization time from 1 h to 6 h at 100 ºC in static conditions. The samples obtained were characterized by X-ray diffraction (XRD), X-ray fluorescence (FRX), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). From the results obtained, it was possible to observe that the syntheses were carried out successfully. The use of Clinoptilolite in the synthesis of zeolites is an innovative, economically viable and environmentally friendly process, valuing a material that exists in large quantities and that is still little explored by industries.